Analysis of the characteristics of connotation evolution of agricultural modernization with Chinese characteristics in the 70 years since the founding of New China - Yongmu Jiang; Lu Yang; Zhang Xiaolei (China Political Economy (CPE), 2020)
Purpose With the development of social productive forces and the advancement of agricultural practices since the founding of New China, the connotation of agricultural modernization with Chinese characteristics has undergone a process from formation to continuous expansion and deepening. Design/methodology/approach Its evolution can be roughly divided into four stages: the exploration stage, the formation stage, the establishment stage and the deepening stage. The historical evolution of the connotation of agricultural modernization with Chinese characteristics demonstrates four typical characteristics, namely increasingly scientific logical premise, continuously diversified orientations, increasingly improved core contents and progressively maturing strategies of development. Findings The achievements of agricultural modernization have laid a solid foundation for China's industrial modernization and the rapid development of the national economy. Meanwhile, the authors have identified through practical exploration a path of agricultural modernization with Chinese characteristics. In recent years, academic research on the connotation of agricultural modernization with Chinese characteristics has gradually heated up, and relevant achievements have emerged constantly. Originality/value The Communist Party of China (hereinafter "CPC") has placed considerable emphasis on agricultural issues and has been committed to promoting agricultural modernization since the founding of New China. Through long-term persistence and unremitting efforts, China has made remarkable achievements in agricultural development: significantly improved agricultural production conditions and agricultural output capacity, constantly optimized agricultural structure and steadily increased the income of farmers.
Keywords: 330; Agricultural modernization; Agricultural modernization with Chinese characteristics; Chinese characteristics; Modernization of agriculture and rural areas